Oncolytic influenza virus infection restores immunocompetence of lung tumor-associated alveolar macrophages. (4th May 2018) - Masemann, Dörthe; Köther, Katharina; Kuhlencord, Meike; Varga, Georg; Roth, Johannes; Lichty, Brian Dennis; Rapp, Ulf Rüdiger; Wixler, Viktor; Ludwig, Stephan
ABSTRACT: Non-small-cell lung cancer (NSCLC) is the most frequent type of lung cancer and demonstrates high resistance to radiation and chemotherapy. These tumors evade immune system detection by promoting an immunosuppressive tumor microenvironment. Genetic analysis has revealed oncogenic activation of the Ras/Raf/MEK/ERK signaling pathway to be a hallmark of NSCLCs, which promotes influenza A virus (IAV) infection and replication in these cells. Thus, we aimed to unravel the oncolytic properties of IAV infection against NSCLCs in an immunocompetent model in vivo . Using Raf-BxB transgenic mice that spontaneously develop NSCLCs, we demonstrated that infection with low-pathogenic IAV leads to rapid and efficient oncolysis, eliminating 70% of the initial tumor mass. Interestingly, IAV infection of Raf-BxB mice caused a functional reversion of immunosuppressed tumor-associated lung macrophages into a M1-like pro-inflammatory active phenotype that additionally supported virus-induced oncolysis of cancer cells. Altogether, our data demonstrate for the first time in an immunocompetent in vivo model that oncolytic IAV infection is capable of restoring and redirecting immune cell functions within the tumor microenvironment of NSCLCs.